Gender and nonmedical prescription opioid use and DSM-5 nonmedical prescription opioid use disorder: Results from the National Epidemiologic Survey on Alcohol and Related Conditions – III. (1st November 2015) - Kerridge, Bradley T.; Saha, Tulshi D.; Chou, S. Patricia; Zhang, Haitao; Jung, Jeesun; Ruan, W. June; Smith, Sharon M.; Huang, Boji; Hasin, Deborah S.
Highlights: We examine prevalence, correlates, comorbidity and treatment of NMPOU. We examine DSM-5 NMPOUD among men and women. Prevalences of 12-month and lifetime NMPOU were greater among men than women. Rates of NMPOUD did not differ between men and women. MDD, persistent depression and bipolar I disorder were associated with NMPOU and NMPOUD among men. Abstract: Background: Little is known about sex-specific risk for nonmedical prescription opioid use (NMPOU) and DSM-5 nonmedical prescription opioid use disorder (NMPOUD). The objective of the present study was to present prevalence, correlates, psychiatric comorbidity, treatment and disability of NMPOU and DSM-5 NMPOUD among men and women. Methods: Nationally representative sample of the U.S. Results: Prevalences of 12-month and lifetime NMPOU were greater among men (4.4%, 13.0%) than women (3.9%, 9.8%), while corresponding rates of DSM-5 NMPOUD did not differ between men (0.9%, 2.2%) and women (0.9%, 1.9%). Regardless of time frame and sex, NMPOU and NMPOUD generally decreased with age and were lower among Blacks, Asians/Pacific Islanders and Hispanics, and respondents with lower socioeconomic status. Among men with NMPOU, rates were lower among respondents in the Northeast and South and among those previously married (lifetime). Across time frames and gender, NMPOU and NMPOUD were generally associated with other substance use disorders, posttraumatic stress and borderline, schizotypal and antisocial personality disorders, but associated with major depressive disorder, persistent depression and bipolar I disorder only among men. Disability increased with NMPOU frequency and NMPOUD severity. Only 7.6% and 8.2% of men and women with NMPOU ever received treatment, while 26.8% and 31.1% ever received treatment for NMPOUD. Conclusions: NMPOU and NMPOUD are highly disabling, associated with a broad array of sex-specific and shared correlates and comorbidities and largely go untreated in the U.S. Valid assessment tools are needed that include gender as a stratification variable to identify NMPOU and NMPOUD.